Equalization versus Normalization: Facebook and the 2013 Israeli Elections. (15th September 2015) - Samuel-Azran, Tal; Yarchi, Moran; Wolfsfeld, Gadi
The question of whether social media grant challengers a fair opportunity to compete with incumbents, thus promoting equalization rather than normalization, is a key issue in studies of the web's contribution to democratic systems. To contribute to the current debate, whose evidence so far strongly supports the normalization hypothesis, we examined the ability of the five leading political candidates in Israel popularity to promote engagement to their messages on social media by measuring Likes and Shares on their Facebook posts during the 2013 election campaign. Surprisingly, we found that first-time candidate, Naftali Bennett, achieved statistically similar engagement levels as achieved by PM Netanyahu, measured by the two Facebook measures mentioned above, and attracted dramatically more Likes than Netanyahu during the campaign. Similarly, first-time contender Yair Lapid's messages promoted equal levels of engagement as did the messages of opposition leader Shelly Yachimovich. The study indicates the ability of challengers to generate similar engagement levels as incumbents through social media campaigns, an encouraging result that illustrates the democratizing potential of social media.